The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1467-629x.2006.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Active investment manager portfolios and preferences for stock characteristics

Abstract: The present study investigates the stock characteristic preferences of institutional Australian equity managers. In aggregate we find that active managers exhibit preferences for stocks exhibiting high-price variance, large market capitalization, low transaction costs, value-oriented characteristics, greater levels of analyst coverage and lower variability in analyst earnings forecasts. We observe stronger preferences for higher volatility, value stocks and wider analyst coverage among smaller stocks. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…, 1989; Bennett et al. , 2003; Pinnuck, 2004; Brands et al. , 2006) could also take into account idiosyncratic volatility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1989; Bennett et al. , 2003; Pinnuck, 2004; Brands et al. , 2006) could also take into account idiosyncratic volatility.…”
Section: Discussionmentioning
confidence: 99%
“…, 1989) and Australia (Pinnuck, 2004) find that institutional investors exhibit a preference for securities with low volatility, although more recent studies by Bennett et al. (2003) for the US and Brands et al. (2006) for Australia indicate a shift in preference among institutional investors for stocks with high volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the size of the funds in terms of funds under management, the sample represents five of the top 10 Australian institutional fund managers, four ranked 11‐20, five ranked 21‐30 and the remainder are outside the largest 30 managers. A more detailed description of the database is available in Gallagher and Looi (2006) and Brands et al (2006). Comparison of the return on the funds in our sample and the broader population of investment funds provided by Mercer Investment Consulting showed that the two sets of returns were almost identical.…”
Section: Data and Sample Descriptionmentioning
confidence: 92%
“…These indices are constructed to provide an equity performance benchmark for fund managers investing on the Australian Securities Exchange (ASX). According to Brands et al (2006), 5% of the funds in the Portfolio Analytic Database are benchmarked to the S&P/ASX 100, 17% to the S&P/ASX 200 and 78% to the S&P/ASX 300. The study, therefore, uses the S&P/ASX 200 index and the S&P/ASX 300 index as benchmark market portfolios.…”
Section: Data and Sample Descriptionmentioning
confidence: 99%
“…For example, Brands et al . () examine the role of GICS industry classifications in the design of a portfolio and document that GICS classification reflects better the industry composition of the ASX and has an important impact on the stockholdings of Australian institutional investment managers. The most recent study by Dou et al .…”
mentioning
confidence: 99%